Fenomena-Fenomena Metafisika Dalam Al Qur’an - Antok Listyantanto; Syarifuddin Syarifuddin (Jurnal Budi Pekerti Agama Islam, 2024)
Metaphysics is a part of the philosophy of science that studies reality. Metaphysics is a part of philosophy about the nature behind physics (which appears). This essence is usually abstract and beyond the reach of ordinary human experience. This phenomenon is the focus of this article, so that it becomes a discussion that can be accepted by humans in general. This paper uses library research (library research) with data sources in the form of scientific articles, books, documents, journals and other sources of a library nature. The data was collected and then analyzed in depth using content analysis techniques and presented descriptively. The research results show that the phenomenon of the revelation of the Koran itself contains metaphysical elements such as the nature of God, His creation and humans so that metaphysics cannot be separated from the practical life of the Islamic religion. The beauty and value of a process in Islam in studying the Koran and and position on earth, namely as servants and caliphs.